Diagnostic delay in inflammatory bowel disease increases the risk of intestinal surgery - Lee, Dong-won (World J Gastroenterol, 2017)
AIM: To investigate the factors affecting diagnostic delay and outcomes of diagnostic delay in inflammatory bowel disease (IBD) METHODS: We retrospectively studied 165 patients with Crohn’s disease (CD) and 130 patients with ulcerative colitis (UC) who were diagnosed and had follow up durations > 6 mo at Korea University Ansan Hospital from January 2000 to December 2015. A diagnostic delay was defined as the time interval between the first symptom onset and IBD diagnosis in which the 76(th) to 100(th) percentiles of patients were diagnosed. RESULTS: The median diagnostic time interval was 6.2 and 2.4 mo in the patients with CD and UC, respectively. Among the initial symptoms, perianal discomfort before di-agnosis (OR = 10.2, 95%CI: 1.93-54.3, P = 0.006) was associated with diagnostic delays in patients with CD; however, no clinical factor was associated with diagnostic delays in patients with UC. Diagnostic delays, stricturing type, and penetrating type were associated with increased intestinal surgery risks in CD (OR = 2.54, 95%CI: 1.06-6.09; OR = 4.44, 95%CI: 1.67-11.8; OR = 3.79, 95%CI: 1.14-12.6, respectively). In UC, a diagnostic delay was the only factor associated increased intestinal surgery risks (OR = 6.81, 95%CI: 1.12-41.4). CONCLUSION: A diagnostic delay was associated with poor outcomes, such as increased intestinal surgery risks in patients with CD and UC.